Smartphone monitoring: companies and products (The journal of offender monitoring, 2022)
We asked the companies participating in this year’s smartphone survey to tell us about themselves and their products. Here, in their own words, are their missions, markets, and monitoring solutions, Acivilate Pokket; BI SmartLINK; BI Mobile; Buddi Eagle Mobile and Check In; cFIVE Catalyst; Corrisoft AIR® Mobile, AIR® Check-In and AIR® Connect; eHawk RePath; SCRAM TouchPoint and SCRAM Ally®; Securus Monitoring EnrolLink® and VeriTracksTM; Shadowtrack EnrolleeApp and ShadowTether; SuperCom PureTrack and Pure Protect; Track Group Empower, Socrates 360, BACtrack, and Intellitrack; TRACKtech TRACK phone, TRACKtether and Victim/Officer Notification App. Contact information is provided with each profile.